2021
DOI: 10.3390/polym13193373
|View full text |Cite
|
Sign up to set email alerts
|

Colour Stabilisation of Surface of Four Thermally Modified Woods with Saturated Water Vapour by Finishes

Abstract: This paper deals with the influence of the type of transparent surface finish on the change of colour of the surfaces of native wood, and thermally treated wood, with saturated water vapour. In the experiment, alder, European beech, Paper birch, and Norway maple wood were thermally treated at a temperature of 135 °C under saturated water vapour for six hours. Three various types of surface finishes (acrylic-polyurethane, polyacrylic and aldehyde resin, and alkyd resin) were applied onto the wood surfaces. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…There were also confirmed significant impacts for wood species, lacquer/coating system type, lacquer modification, and wood surface pre-treatment with pigment and stain mordants on colour change during accelerated ageing. The better colour resistance of transparent surface-finished wood confirms the already recognised fact that darker wood surfaces are more stable [28][29][30]46]. In addition, it may be affected by the type and amount of topcoat applied [47,48].…”
Section: Beforesupporting
confidence: 64%
See 2 more Smart Citations
“…There were also confirmed significant impacts for wood species, lacquer/coating system type, lacquer modification, and wood surface pre-treatment with pigment and stain mordants on colour change during accelerated ageing. The better colour resistance of transparent surface-finished wood confirms the already recognised fact that darker wood surfaces are more stable [28][29][30]46]. In addition, it may be affected by the type and amount of topcoat applied [47,48].…”
Section: Beforesupporting
confidence: 64%
“…Photo-oxidative degradation and yellowing or discolouration in polyurethane coatings upon UV irradiation is a general phenomenon. In our previous study [ 30 ], discolouration of a finishing system based on polyacrylic, and aldehyde resin resulted mainly from the photo yellowing of underlying untreated and HTT-treated wood due to sunlight and increased with irradiation time. Furthermore, the results of the study [ 46 ] showed that an accelerated ageing process with simulation of indoor conditions induced significant discolouration of surface-treated wood, both coated with solvent-based polyurethane and water-based lacquers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there are no reports on the technological properties of thermally modified wood in nitrogen atmosphere, especially finished with different coatings. The colour stability of thermally modified wood in overheated steam and covered with various types of coatings was widely analysed [37,38]. The influence of wood heat treatment and coatings on hardness, scratch resistance [39], abrasion resistance [40] was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Vidholdová et al [4] TM spruce wood lost individual hemicelluloses in this order: arabinose > mannose~glucose > xylose~galactose due to their depolymerisation, creation of internal ethers, and other rearrangement products, and finally, decomposition into volatile compounds [18][19][20]. Changes in the molecular level of TM wood have also been observed through infrared spectroscopy [21,22], and indirectly through colour changes [23,24], or creation of splits and cracks [25,26]. Details of the brittle behaviour of TM wood were revealed by means of images of fracture surfaces at the ultrastructural level.…”
Section: Introductionmentioning
confidence: 99%